Liver X receptor activation stimulates iron export in human alternative macrophages - Bories, Gael (Lippincott Williams & Wilkins, 2013)
RATIONALE: In atherosclerotic plaques, iron preferentially accumulates in macrophages where it can exert pro-oxidant activities. OBJECTIVE: The objective of this study is, first, to better characterize the iron distribution and metabolism in macrophage sub-populations in human atherosclerotic plaques and, second, to determine whether iron homeostasis is under the control of nuclear receptors, such as the Liver X Receptors (LXR). METHODS AND RESULTS: Here we report that iron depots accumulate in human atherosclerotic plaque areas enriched in CD68 and Mannose Receptor (MR) positive (CD68+MR+) alternative M2 macrophages. In vitro IL-4 polarization of human monocytes into M2 macrophages also resulted in a gene expression profile and phenotype favouring iron accumulation. However, upon iron exposure, M2 macrophages acquire a phenotype favouring iron release, through a strong increase in ferroportin expression, illustrated by a more avid oxidation of extra-cellular LDL by iron-loaded M2 macrophages. In line, in human atherosclerotic plaques, CD68+MR+ macrophages accumulate oxidized lipids, which activate Liver X Receptors (LXRα and LXRβ), resulting in the induction of ABCA1, ABCG1 and ApoE expression. Moreover, in iron-loaded M2 macrophages, LXR activation induces nuclear factor erythroid 2-like 2 (NRF2) expression, hence increasing ferroportin expression, which, together with a decrease of hepcidin mRNA levels, promotes iron export. CONCLUSIONS: These data identify a role for M2 macrophages in iron handling, a process which is regulated by LXR activation.